EDUKASI MENGENALKAN ENURESIS PADA ORANGTUA YANG MEMILIKI ANAK USIA DIATAS 4 TAHUN DI RAUDHATUL ATHFAL MELATI YPNH BATURAJA - Suparno, Suparno -; Estiani, Meilina; Rustiaty, Nelly; Aisyah, Aiysah; Rosa, Eni Folendra (Jurnal Likhitaprajna, 2024)
Functional nocturnal enuresis is a condition in which children over the age of 4 without physical abnormalities or organic disease experience involuntary urine output during the day or night. Bedwetting can result in loss of self-confidence, damage relationships, and affect children's social developmen. Suparno, et al, found that 22.7% of RA Melati YPNH Baturaja were unable to control enuresis . There are several students who wet the bed when they wake up at night and parents have never been educated about enuresis. The aim of this activity is to increase parents' knowledge, attitudes and abilities about Enuresis. Methods used: lecture, question and answer, and self and group reflection. It was found that the level of insufficient knowledge before education was 100%. After education, the level of knowledge was good 64.28%, sufficient 32.14% and poor 3.57%. There was an increase in the percentage of knowledge of 96.42%. Proactive actions taken by parents to understand bedwetting and actively participate in dealing with bedwetting. Of the 10 children who still wet the bed after evaluation between 2 - 4 months, it was found that 90% of the children no longer wet the bed. The forms of behavioral intervention are as follows: walking (24.13%), lifting (3.44%), reward system (10.34%), limiting drinking before bed (24.13%), limiting playing time (10.34) and Urination before bed (31.03%).